PENERAPAN PROFIT SHARING BERBASIS AL-ADHL PADA PRODUK MUDHARABAH DI PERBANKKAN SYARIAH - Sandi, Ahmad; Abdullah, Muhammad Wahyuddin; K, Amiruddin (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
The purpose of this study is to find out how to Apply Al-Adhl-Based Profit Sharing on Mudharabah Products in Sharia Banking. The research method used is qualitative research using literature studies with the aim of describing the problem being researched. Data collection techniques with literature studies from various sources such as books, the internet, and research journals that have the same topic as those discussed by the researcher. The purpose of the study is to find out the Application of Al-Adhl-Based Profit Sharing in Mudharabah Products in Sharia Banking. From the results of the discussion, it is shown that the application of profit sharing based on Al-Adhl (fair) in Mudharabah Products in Sharia Banking, has not fully run in accordance with the mechanism and principles of fairness, where in the distribution of revenue, the income distributed to shahibul mal and mudharib is still not fully in accordance with the Qur'an and Sunnah. There is still a lack of character in fulfilling the mandate and a sense of guilt in committing fraud among the community, so that it affects obedience in carrying out the agreement between the two parties of shahibul mal and mudharib